Establishing Requirements for Breast Centers in Low- and Middle-Income Countries: A South African Perspective - Sarah Nietz; Jenny Edge; Ines Buccimazza; Georgia Demetriou; Mariza Tunmer; Jacqueline Smilg; Duvern Ramiah; Peter Schoub; Shane A. Norris; Paul Ruff (JCO Global Oncology)
PURPOSEIn South Africa, breast care lacks governance and standardization, necessitating urgent improvements in patient outcomes. Quality improvement initiatives are urgently needed in low- and middle-income countries (LMICs), but requirements for breast centers in lower resource settings remain undefined and must be tailored to local environments. This consensus document outlines the role and requirements of breast centers in LMICs and presents a step-by-step implementation plan.METHODSThe literature was systematically reviewed, and the primary review team tabulated international accreditation standards alongside the 2018 South African Clinical Guidelines for Breast Cancer Control and Management from the South African National Department of Health, along with proposed South African standards. The broader consensus panel consisted of 29 clinical experts and representatives from societies, advocacy, and funders.RESULTSWe categorized requirements into eight broader categories and achieved unanimous consensus on all requirement components, except for 1 abstention in the general specialist and expertise category. We were unable to reach consensus on the patient volume requirements for radiologists as well as for medical and clinical/radiation oncologists. Volume requirements for clinical and radiation oncologists were later provided by the South African Society of Clinical and Radiation Oncology (SASCRO), along with the volume requirements submitted by the participating radiologists. We also achieved unanimous consensus for the Breast Interest Group of Southern Africa (BIGOSA) to house the initial project implementation. This consensus document is endorsed by BIGOSA, SASCRO, and the Cancer Association of South Africa.CONCLUSIONWe emphasize the importance and necessity of breast centers in resource-constrained environments, outline the first set of requirements for breast centers tailored to LMICs in sub-Saharan Africa, and present a feasible and detailed plan for initial implementation.